Model Alur Kerja Penanganan Bukti Digital Untuk Data Multimedia - Dirman Dirman; Yudi Prayudi; Erika Ramadhani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Multimedia crime through digital platforms and transmission is a severe and detrimental condition. Nowadays, digital multimedia cases have received much attention, especially in handling multimedia evidence that can be used as an instrument to determine scientific truth in court. In addition, multimedia digital evidence is straightforward to modify using applications that can be used freely so that the authenticity of digital data can be damaged or lost. The challenge faced by investigators in handling multimedia digital evidence is the variable demands for the investigation's validity, handling, documentation, and reporting processes. Like handling procedures in general, digital multimedia case investigations require a workflow so that the investigation stages can be well controlled. This study examines the framework, standard operating procedures, and workflows for handling digital evidence. The results of the mapping and study are used as a workflow model for handling digital evidence for multimedia data by using the design thinking method with the Business Process Model and Notation (BPMN) approach in getting the relationship between actors, digital evidence, and workflows.